The Effect of Accounting Information and Organizational Culture on Decision Making - Teresa Paulina Sihombing; Nasirwan Nasirwan; Chandra Situmeang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study examines the educational foundation's organizational decision making model that is the influence of accounting information and organizational culture on decision making. This research is a quantitative study with descriptive and inferential analysis. The sample of this study was 72 Catholic education foundations in Indonesia, which were tested by Partial Least Square (PLS) based analysis and data processing methods with the Smart PLS 3.0 program. This study obtains some empirical evidence, namely, first, accounting information significantly influences decision making. These results are consistent with the theory that the main purpose of the foundation's financial statements is to provide relevant information to meet the foundation's internal and external interests to help decision makers make the best decisions for the organization. Second, organizational culture significantly influences decision making. This result is in line with organizational culture theory which states that organizational culture is a value that is used as a reference in all decisions and actions of members of the organization and that reflects the goals, identity, and standard of evaluation of everything in the organization. So it was concluded that the best decision was a decision made based on accounting information and organizational culture at a Catholic education foundation in Indonesia